2020
DOI: 10.1007/s10803-020-04684-0
|View full text |Cite
|
Sign up to set email alerts
|

What Happens at a Dental Surgery When the Patient is a Child with Autism Spectrum Disorder? An Italian Study

Abstract: Oral health care can be a difficult experience for a child with Autism Spectrum Disorder (ASD), for their family and for the dentist. The purpose of this study is to provide an understanding of the challenges experienced by the three aforementioned figures during oral care treatment. A cohort of 275 parents of typical development children (TD), 57 parents of children with ASD (3–15 years old) and by 61 dentists, completed two different multiple choices questionnaires. The data obtained show a great difficulty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
0
6
0
7
Order By: Relevance
“…The data presented here are an excellent starting point for improving the approach and treatment of patients with disabilities. The literature has already demonstrated that surveys are useful to better understand various problems and evaluate the appropriate solutions [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here are an excellent starting point for improving the approach and treatment of patients with disabilities. The literature has already demonstrated that surveys are useful to better understand various problems and evaluate the appropriate solutions [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Finding a dental practitioner willing and competent to treat Autistic individuals has been proven to be a barrier to accessing dental care. Of the 16 papers, 8 papers reported that finding a dentist willing or competent to treat an Autistic individual was a major concern for parents and carers [ 23 , 27 , 28 , 31 , 32 , 34 , 36 , 40 ]. Kind et al noted that that only 10% of American general dentists perform dental treatment for individuals with special needs including ASD, 21% of parents were dissatisfied with the dental care they received and 88% of parents could accurately predict a child’s cooperation for dental treatment [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kind et al noted that that only 10% of American general dentists perform dental treatment for individuals with special needs including ASD, 21% of parents were dissatisfied with the dental care they received and 88% of parents could accurately predict a child’s cooperation for dental treatment [ 34 ]. Indeed, as described by Logrieco, parents of Autistic individuals reported experiencing a great deal of stress during a dental visit due to concerns over their own knowledge of preventative oral care and/or the preparedness of the dental practitioner to accommodate their child’s potential fears of the dental environment, communication difficulties, aggressive behaviors, difficulties expressing oral pain and/or sensory sensibilities [ 36 ]. Alshatrat et al also highlighted parents’ identification of a lack of knowledge, lack of specialised staff and inadequate facilities to support the treatment of individuals with disabilities in their case-controlled study [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Difficulty in managing children's behaviours, including non‐co‐operation and compliance with dental procedures, was one of the most frequently reported barriers to dental care access cited by parents and dentists. 25 , 27 , 28 , 30 , 32 , 33 , 35 , 36 , 37 , 42 , 43 , 46 , 48 , 53 , 54 , 55 , 56 A US study 33 found that autistic children with more behavioural difficulties had an increased odds of unmet dental needs compared to those with autism who showed behaviours similar to same‐aged peers (odds ratio: 3.35, 95% confidence interval: 1.69, 6.67). The uncooperative behaviours of some autistic children affect the ability of practitioners to carry out the dental procedures needed to care for their teeth, 25 with obvious implications for OH.…”
Section: Resultsmentioning
confidence: 99%